Property rights: Debates in Chile regarding the german experience - Soto Velasco, Sebastián; Muñoz Massouh, Ana María (Derecho Público Iberoamericano, 2019)
This paper critically examines two recently constitutional amendment bills. Both bills include in the Constitution, following the German Fundamental Law, a provision stating that property must serve the common good. This research studies the foundations of regulation of property in German constitutionalism and the social function provision in Chilean constitutionalism. Both perspectives give us room to conclude that current regulation of the social function, which allow limitations to property rights, is not different to the “common good” provision in the Fundamental Law of Germany. Then, such amendment does not contribute to the Chilean regulation of property right and, on the contrary, it could weak the protection of property.